2017
DOI: 10.1103/physrevd.95.124032
|View full text |Cite
|
Sign up to set email alerts
|

Horizon instability of extremal Reissner-Nordström black holes to charged perturbations

Abstract: We investigate the stability of highly charged Reissner-Nordström black holes to charged scalar perturbations. We show that the near-horizon region exhibits a transient instability which becomes the Aretakis instability in the extremal limit. The rates we obtain match the enhanced rates for nonaxisymmetric perturbations of the near-extremal and extremal Kerr solutions. The agreement is shown to arise from a shared near-horizon symmetry of the two scenarios.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 85 publications
(118 reference statements)
2
32
0
Order By: Relevance
“…This implies that infalling observers experience large gradients [15]. However, scalars constructed from the field remain small, since all such quantities will inherit self-similarity from (14) with some exponent h ′ = nh where n is a positive integer that counts the number of times the field appears in the formula for the scalar invariant. The invariant then takes the general form (20) with h → nh, i.e.…”
Section: Aretakis Instability From Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that infalling observers experience large gradients [15]. However, scalars constructed from the field remain small, since all such quantities will inherit self-similarity from (14) with some exponent h ′ = nh where n is a positive integer that counts the number of times the field appears in the formula for the scalar invariant. The invariant then takes the general form (20) with h → nh, i.e.…”
Section: Aretakis Instability From Symmetrymentioning
confidence: 99%
“…In defining holographic propagators by limits involving multiplication by x h , we have assumed boundary conditions such that the field goes as x −h at large x in boundary-adapted coordinates and gauge. The scaling self-similarity (14) of the bulk-boundary propagator means that…”
Section: E Scaling Dimensionmentioning
confidence: 99%
“…The original result (1.1) held only for initial data that was non-zero on the event horizon, but it soon became clear that the instability persists for data supported arbitrarily far away [8][9][10], although sometimes with different rates [11]. The result was also extended to near-extremal black holes, where the growth occurs transiently (for a time of order the inverse temperature) near the horizon [8,[12][13][14]. Although the precise power laws differ from example to example, this typical behavior of successive derivatives growing one power of v faster has now been seen in a wide variety of perturbation problems involving (near-)extremal black holes, and is known as the Aretakis instability.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to study the late time behavior of such black holes analytically using the weakly broken conformal symmetry of their near-horizon region. In particular, gravitational backreaction is accounted for within the Jackiw-Teitelboim model for near-horizon, near-extremal dynamics coupled to bulk matter.types of perturbation fields [14], [15], [16], [17], and in particular in [18] it was shown that a massless scalar displays Aretakis behavior on any extreme BH background. The picture arising from these studies is that the Aretakis behavior is a general feature of extremal BHs, in the following sense: the k-th transverse-to-the-horizon derivative of the perturbation, at late times on the horizon, behaves (no worse than 1 )where ∆ − is a negative k-independent, fixed non-universal constant.…”
mentioning
confidence: 99%
“…types of perturbation fields [14], [15], [16], [17], and in particular in [18] it was shown that a massless scalar displays Aretakis behavior on any extreme BH background. The picture arising from these studies is that the Aretakis behavior is a general feature of extremal BHs, in the following sense: the k-th transverse-to-the-horizon derivative of the perturbation, at late times on the horizon, behaves (no worse than 1 )…”
mentioning
confidence: 99%